THE SEXUAL VIOLENCE IN SARAH POLLEY’S WOMEN TALKING (2022) MOVIE: A FEMINIST PERSPECTIVE - Utami, Cahya Yulias Putri; Setyabudi, Titis (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The movie Women Talking (2022) is based on a true story from a Mennonite colony in Bolivia, where from 2005 to 2009, women were drugged with animal anesthetic spray and raped. They woke up with pain, bruising and bleeding. The purpose of this study is to identify the types of sexual violence in the movie, secondly to find out the impact of sexual violence on the characters in the movie and finally to describe how sexual violence is depicted in the movie. This research uses descriptive qualitative method. The data source of this research is the movie Women Talking (2022) by Sarah Polleys. The theory of this research uses Tong's feminism theory (2013). The results showed that there are 6 types of sexual violence in the film Women Talking, namely spiking, rape, sexual exploitation, forced pregnancy and abortion, sexual punishment and torture, and incest. There are 4 impacts of sexual violence experienced by the main character, namely impacts on mental health, impacts on physical health, impacts on behavior, and impacts on society. Then the depiction of sexual violence in this film is seen through themes, characters, settings, plot, and moral values. This movie shows us how feminism struggles against sexual violence experienced by women and provides a strong view of the challenges faced by women in facing sexual violence.